Postural Stabilization Differences in Idiopathic Parkinson’s Disease and Progressive Supranuclear Palsy during Self-Triggered Fast Forward Weight Lifting - Kammermeier, Stefan; Dietrich, Lucia; Maierbeck, Kathrin; Plate, Annika; Lorenzl, Stefan; Singh, Arun; Ahmadi, Ahmad; Bötzel, Kai (Frontiers in Neurology, 2018)
Progressive Supranuclear Palsy (PSP) and late-stage Idiopathic Parkinson’s Disease (IPD) are neurodegenerative movement disorders resulting in different postural instability and falling symptoms. IPD falls occur usually forward in late-stage, whereas PSP falls happen in early stages, mostly backward, unprovoked and with high morbidity. Self-triggered, weighted movements appear to provoke falls in IPD, but not in PSP. Repeated self-triggered lifting of a 0.5-1kg weight (<2% of body weight) with the dominant hand was performed in 17 PSP, 15 IPD with falling history and 16 controls on a posturography platform. PSP showed excessive force scaling of weight and body motion with high-frequency multi-axial body sway, whereas IPD presented a delayed-onset forward body displacement. Differences in center of mass displacement apparent at very small weights indicate that both syndromes decompensate postural control already within stability limits. PSP may be subject to specific postural system devolution. IPD are susceptible to delayed forward falling. Differential physiotherapy strategies are suggested.